Legal Protection for Buyers Who Suffer Harms in Buying and Selling Transactions on Social Media (From a Civil Law Perspective) - Immanuel Lamhot Sitanggang; Jinner Sidauruk; Roida Nababan (PT FORMOSA CENDEKIA GLOBAL, 2025)
The development of digital technology has increased buying and selling transactions through social media; however, it has also raised various risks for buyers, such as products that do not match the description, defective goods, and fraud. This study aims to analyze the legal protection for disadvantaged buyers and the legal remedies available in social media transactions from a civil law perspective. The research method used is normative legal research with a statutory approach and qualitative juridical analysis of applicable regulations. The results show that legal protection for disadvantaged buyers is regulated under various laws, including the Civil Code (KUHPerdata), the Consumer Protection Law (UUPK), and the Information and Electronic Transactions Law (UU ITE). This legal protection includes preventive measures, such as regulations governing rights and obligations in electronic transactions, as well as repressive measures, such as dispute resolution mechanisms for affected buyers. Legal remedies available to buyers include litigation through the court system and non-litigation approaches such as negotiation, mediation, and arbitration. With clear legal protection and stricter supervision by the government and social media platforms, online buying and selling transactions are expected to be safer, more transparent, and provide legal certainty for all parties involved.